2020
DOI: 10.1113/jp280652
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of skeletal muscle atrophy in response to transient knockdown of the vitamin D receptor in vivo

Abstract: Key points Reduced vitamin D receptor (VDR) expression prompts skeletal muscle atrophy. Atrophy occurs through catabolic processes, namely the induction of autophagy, while anabolism remains unchanged. In response to VDR‐knockdown mitochondrial function and related gene‐set expression is impaired. In vitro VDR knockdown induces myogenic dysregulation occurring through impaired differentiation. These results highlight the autonomous role the VDR has within skeletal muscle mass regulation. Abstract Vitamin D d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 78 publications
2
31
0
1
Order By: Relevance
“…First, there seems to be associations between mutations in the vitamin D receptor and muscle weakness in both humans and mice 54,55 . Second, muscle‐specific knock‐out of the vitamin D receptor in mice deteriorates muscle strength and mass in a manner that resemble sarcopenia 56,57 . The prevailing uncertainty is fuelled by a seeming lack of effects of vitamin D supplementation per se on the muscle transcriptome in vitamin D‐insufficient frail elderly, although also in that study the vitamin D dosage was relatively low (400 IU/day) 58 .…”
Section: Introductionmentioning
confidence: 82%
“…First, there seems to be associations between mutations in the vitamin D receptor and muscle weakness in both humans and mice 54,55 . Second, muscle‐specific knock‐out of the vitamin D receptor in mice deteriorates muscle strength and mass in a manner that resemble sarcopenia 56,57 . The prevailing uncertainty is fuelled by a seeming lack of effects of vitamin D supplementation per se on the muscle transcriptome in vitamin D‐insufficient frail elderly, although also in that study the vitamin D dosage was relatively low (400 IU/day) 58 .…”
Section: Introductionmentioning
confidence: 82%
“…Visual inspection analysis showed that the hind limb size was not clearly different among groups, although the hind limb sizes of HB200 group were bigger than those of other groups. Skeletal muscle atrophy is characterized by reduction in muscle mass and diameter of muscle fiber [26]. Histological examination results of gastrocnemius cross sections showed that the diameters of muscle fiber were greater in NC and HB groups than those of HC group.…”
Section: Effects Of Hb On Muscle Mass and Expression Levels Of Atrophy Related Genesmentioning
confidence: 99%
“…Reduced vitamin D is associated with impaired mitochondrial function in skeletal muscle [ 146 ]. Moreover, vitamin D receptor (VDR) loss-of-function C2C12 myoblasts display severely compromised mitochondrial function [ 147 ], whereas muscle-specific VDR knock down in rodents leads to decreased expression of mitochondrial genes and sarcopenia [ 148 , 149 ]. On the other hand, 25(OH)D administration improves mitochondrial OXPHOS and dynamics in C2C12 myoblasts [ 146 ] ( Figure 3 ).…”
Section: Vitamin Dmentioning
confidence: 99%